Compliance with mass marketing solicitation: The role of verbatim and gist processing - Julia Nolte; Yaniv Hanoch; Stacey A. Wood; Valerie F. Reyna (Brain and Behavior, 2021)
Abstract Introduction Mass marketing scams threaten financial and personal well‐being. Grounded in fuzzy‐trace theory, we examined whether verbatim and gist‐based risk processing predicts susceptibility to scams and whether such processing can be altered. Methods Seven hundred and one participants read a solicitation letter online and indicated willingness to call an “activation number” to claim an alleged $500,000 sweepstakes prize. Participants focused on the solicitation's verbatim details (hypothesized to increase risk‐taking) or its broad gist (hypothesized to decrease risk‐taking). Results As expected, measures of verbatim‐based processing positively predicted contact intentions, whereas measures of gist‐based processing negatively predicted contact intentions. Contrary to hypotheses, experimental conditions did not influence intentions (43% across conditions). Contact intentions were associated with perceptions of low risk, high benefit, and the offer's apparent genuineness, as well as self‐reported decision regret, subjective vulnerability to scams, and prior experience falling for scams. Conclusions Overall, message perceptions and prior susceptibility, rather than experimental manipulations, mattered in predicting scam susceptibility.